Explaining Expulsions of U.S. Diplomatic Personnel from Latin America, 1991–2016. (25th November 2018) - Jordan, Anthony; Tuman, John P.
Abstract : This article examines expulsions of U.S. diplomats from Latin America and the Caribbean between 1991 and 2016. Employing an original data set of expulsions of U.S. diplomatic personnel, the analysis focuses on the number of first‐mover expulsions—cases where the Latin American government was the first to expel a U.S. diplomat in a year. The models are estimated with pooled negative binomial regression with robust standard errors. The results suggest there were more first‐mover expulsions in countries governed by radical, populist‐left presidents. For the radical, populist Left, expulsions offered a low‐cost mechanism to pursue opposition to U.S. influence in Latin America while also giving executives an opportunity to strengthen ties to their electoral base. Results also show that presidential election years had a positive and significant effect. Prior retaliatory expulsions, alleged U.S. interference, other types of executive‐party control, and economic ties with the United States and China had no effect on expulsions. Oil exports to the United States were associated positively with higher expulsion counts, which we attribute to the unwillingness of radical populists—and of the United States—to escalate diplomatic tensions into wider economic conflicts.